อิทธิพลของวิธีการสกัดต่อผลได้การสกัดและฤทธิ์การต้านอนุมูลอิสระของสารสกัดพืชสมุนไพรไทย - ผลประไพ ชนัญ; อุ่นทวี ศรัณยู; สุขเอม จุฑามาส; ทองสอง ภานุวัฒน์ (Thai Journal of Science and Technology, 2019)
Abstract Free radical accumulation has been known as a cause of untimely death, therefore the consumption of antioxidants from herbal plants could be the promising choices for health promotion. This research focused on studying influences of extracting methods on extraction yield and antioxidant activity of the extracts obtained from licorice roots, cloves and chrysanthemum flowers. Additionally, the effect of supercritical CO2 extraction process on the characteristic of chrysanthemum flower extract was compared to other processes including maceration, shaking extraction and Soxhlet extraction. The results revealed that the maceration method used in extracting chrysanthemum flower gave the highest extraction yield [9.70 % (w/w)], with low IC50 value (78.28 µg/mL), while the clove flower was found to obtain high IC50 value (11.55 µg/mL). However, the extracting yield of the clove flower with maceration method gave the moderate yield [8.05 % (w/w)]. As a result, chrysanthemum flower was then selected to study on a variety of extraction methods. The increasing on the extraction pressure of supercritical CO2 extraction process was found to increase the extraction yield and antioxidant activity of chrysanthemum extract. This extracting condition also caused many substances in chrysanthemum flower to be dissolved. However, the results also showed that the Soxhlet method used in extracting chrysanthemum flower gave the highest yield of 23.09 % (w/w). The increment of chrysanthemum flower extraction yield, supercritical CO2 flow rate, time length of the extraction process and the amount of dry chrysanthemum flower powder should be increased. Keywords: extraction method; extraction yield; antioxidant activity; herbal plant; chrysanthemum flower